Effectiveness of two synthetic hormones (LHRHA and Ovaprim) on induced breeding of the Bornean spotted barb, Puntius sealei (Herre, 1933) - Abit, Lirong Yu; Ahmad Nasir, Ahmad Syafiq; Grinang, Jongkar ak; Latif, Kamil (Genesis Publishing Consortium Limited, 2024)
Puntius sealei or the Bornean Spotted Barb is a cyprinid of incidental economic importance throughout its distribution range within freshwater habitats of the island of Borneo. The aim of this study was to compare the effectiveness of two synthetic hormones (LHRHA and Ovaprim (SGnRHA + Domperidone) (Manufacturer: Syndel) in inducing ovulation and spermiation in adult fish of this species. The present study was conducted at the wet lab, Faculty of Resources Science and Technology UNIMAS Campus. The study comprised a single experimental trial. A total of 12 pairs of adult fish (12 males and 12 females) were used in this study. The fish were randomly paired at a ratio of 1 male to 1 female fish. 6 pairs of fish were randomly selected and injected intramuscularly with LHRHA while the remaining 6 pairs were injected intramuscularly with Ovaprim. The number of spawnings occurring and early embryonic development was observed and compared. The results showed that Ovaprim successfully induced spawning with viable fertilized eggs in Puntius sealei whereas LHRHA did not induce any spawning.